2006
DOI: 10.3844/ojbsci.2006.51.55
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethanol Extract of Vinca rosea on Wound Healing in Diabetic Rats

Abstract: Vinca rosea (Catharanthus roseus L.) is native to the Caribbean Basin and has historically been used to treat a wide assortment of diseases. European herbalists used the plant for conditions as varied as headache to a folk remedy for diabetes. The objective of the study is to evaluate the diabetic wound healing activity of Vinca rosea using the excision wound model in a streptozotocin induced diabetic rats. The animals were weight matched and placed into five groups (n=6 per group). Animals in groups 1 and 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…The skin tightening and skin texture and lusture restoration effects of V. amygdalina obtained in this study is suggested to be as a result of the excess fat reduction effects (Kim et al, 2006); the immune defence properties; the body organ repair properties (Liu et al, 2005;Nayak, 2006;Sudha et al, 2009;Tong-Un et al, 2010) and the direct skin tightening effects of V. amygdalina leaf extract.…”
Section: Discussionmentioning
confidence: 63%
“…The skin tightening and skin texture and lusture restoration effects of V. amygdalina obtained in this study is suggested to be as a result of the excess fat reduction effects (Kim et al, 2006); the immune defence properties; the body organ repair properties (Liu et al, 2005;Nayak, 2006;Sudha et al, 2009;Tong-Un et al, 2010) and the direct skin tightening effects of V. amygdalina leaf extract.…”
Section: Discussionmentioning
confidence: 63%
“…The exact pathogenesis of the poor wound healing with the diabetic wound is not clearly understood, but evidence from studies involving both human and animal models reveal several abnormalities in the various phases of wound healing process. [8] Taking a clue from the antibacterial and anti-inflammatory activity of the plant leaves as reported in the traditional literature, the present study was planned to evaluate the wound healing property of its ethanolic extract, using normal and diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…The primary phytochemicical screening of leaves shows the presence of tannin alkaloid and terpenoid the result revealed that these are the compound responsible for anti diabetic wound healing activity. Nayak et al (2006) studied antimicrobial and wound healing activity of flower extract of in Sprague Catharanthus roseus Dawley rats. Three wound models such as Excision, incision and dead space were used to assess the wound-healing activity of Catharanthus roseus flower extract.…”
Section: K Ingdom Plantaementioning
confidence: 99%